2017
DOI: 10.1016/j.icarus.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The thermal structure of the Venus atmosphere: Intercomparison of Venus Express and ground based observations of vertical temperature and density profiles

Abstract: Highlights  The Venus International Reference Atmosphere (VIRA) model developed from results of the Venera and Pioneer Venus Orbiter and Multi-Probe missions in early 1980s has been very useful in Venus atmospheric studies for the last several decades. The recent long term monitoring of the Venus atmosphere from Venus Express mission has added a lot of new information about the atmospheric structure above about 40 km altitude and up to nearly 200 km from passive infrared remote sensing, occultation at radio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 126 publications
(38 reference statements)
4
43
0
Order By: Relevance
“…The parameters of the background atmosphere are taken from the values at 70‐km altitude at latitudes <30° of Venus International Reference Atmosphere (Seiff et al, ): The temperature is 229.8 K, the gas constant used for calculating H is 191.3 J·K ‐1 ·kg ‐1 , γ = 1.32, g = 8.67 m/s 2 , T 0 = 229.8 K, and the Brunt‐Väisälä frequency is N B = 0.018 s ‐1 . Though newer data are available (Limaye et al, ), the difference from Venus International Reference Atmosphere is small around the cloud top (65–70 km) at low latitudes according to radio occultations (Imamura et al, ; Tellmann et al, ); we confirmed that the difference hardly changes the results below. The scale height is calculated to be H ~ 5.1 km.…”
Section: Resultssupporting
confidence: 80%
“…The parameters of the background atmosphere are taken from the values at 70‐km altitude at latitudes <30° of Venus International Reference Atmosphere (Seiff et al, ): The temperature is 229.8 K, the gas constant used for calculating H is 191.3 J·K ‐1 ·kg ‐1 , γ = 1.32, g = 8.67 m/s 2 , T 0 = 229.8 K, and the Brunt‐Väisälä frequency is N B = 0.018 s ‐1 . Though newer data are available (Limaye et al, ), the difference from Venus International Reference Atmosphere is small around the cloud top (65–70 km) at low latitudes according to radio occultations (Imamura et al, ; Tellmann et al, ); we confirmed that the difference hardly changes the results below. The scale height is calculated to be H ~ 5.1 km.…”
Section: Resultssupporting
confidence: 80%
“…Such strong hemispherical asymmetries have never been reported on the UV albedo, and their cause is yet to be determined although inhomogeneities in the distribution of an absorber at NIR wavelengths (Titov et al, 2012) cannot be ruled out. The sharp albedo changes displayed in Figure 1c have never been observed before Akatsuki (Limaye et al, 2017), and they were recurrent during the first half of 2016 and absent on UV images of the upper clouds. They involve a 1-4% decrease in the photometrically corrected radiance and, since they moved with zonal speeds ∼10-20 m/s faster than other cloud features, we interpret them as atmospheric waves.…”
Section: Photometric Correctionmentioning
confidence: 62%
“…The region above 58 km is also stable and is dominated by short-vertical scale (< 5 km) fluctuations, being consistent with Venus Express radio occultation experiments . The range of the temperature variation near the top is ~ 50 K, which is smaller than the day-to-day variability of ~ 80 K in the same height region observed by the solar occultation experiment SOIR onboard Venus Express (Mahieux et al 2012;Limaye et al 2017). More measurements are needed to better understand the variability.…”
Section: Atmospheric Profilesmentioning
confidence: 73%